‘Jengah’ (Self-Consciousness) and Its Value Transformation: A Road Toward Good Governance at Bali Province - I Putu Sastra Wingarta; Irwan Abdullah; Djoko Suryo (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2012)
Globalization and its threat continuously endanger Bali, an Island with natural and cultural uniqueness, as well as one of the 33 provinces in Indonesia. This study aims to find out, how big a threat that endangers the contemporary Bali, and the role of ‘jengah’ (self-consciousness) to face the globalization. It is found in the research that ‘jengah’ and its value transformation in it gives positive contribution to face the threat and those values can guarantee the sustainability of Bali uniqueness in the future. The research was conducted at Bali Province Government or ‘Pemprov Bali’. The research showed that by transforming the ‘jengah’ (self-consciousness) values, Bali Province Government succeeded in improving its good governance as well as the apparatuses sense of nationalism. The values also gave the positive impact to prevent the swift threat on Bali uniqueness.